A pragmática-linguística no processamento da linguagem natural: contribuições ao tratamento temático da informação - Rosa, Giovanna Teodoro [UNESP] (Universidade Estadual Paulista (Unesp), 2025)
As atividades do tratamento temático da informação são mediadas pela linguagem natural, que está sujeita a fenômenos como variação linguística e ambiguidade. A automatização destes processos torna-se limitado para o processamento de contextos informacionais e linguagem natural, evidenciando a relevância de investigações comuns à ciência da informação, estudos linguísticos e tecnologia, buscando novos aportes teóricos-metodológicos para a potencialização de atividades representativas. Para isso buscou-se identificar as contribuições pragmáticas-linguísticas nos softwares de análise textual por meio de uma pesquisa bibliográfica e da análise dos softwares Yake!, MAUI, Annif, Medical Text Indexer, KEA, WEKA, Finto AI, Voyant Tools, Cortext, IRaMuTeQ, AntConc, Orange Data Mining e Yoshikoder, o que levou a consideração de que nenhum dos 13 softwares se fundamenta nos conceitos e estudos pragmáticos, embora a presença da linguística de corpus contribua para uma aproximação entre informação, representação e contexto.

The subject representation activities are inherently guided by natural language, whose linguistic variation and ambiguity represent challenges for information representation and retrieval processes. The automation of these processes requires the understanding and processing of informational contexts, highlighting the importance of dialogues between information science, linguistics, and natural language processing technologies. This study investigates to what extent text analysis software incorporates pragmatic-linguistic foundations capable of supporting subject representation activities in natural language. To this end, bibliographic research and a comparative analysis of thirteen tools were conducted: Yake!, MAUI, Annif, Medical Text Indexer, KEA, WEKA, Finto AI, Voyant Tools, Cortext, IRaMuTeQ, AntConc, Orange Data Mining, and Yoshikoder. The results indicate that none of the examined applications is explicitly based on pragmatic theories; however, the presence of methods originating from corpus linguistics is observed, bringing information, representation, and context closer together. It is concluded that, although they offer useful resources for the partial automation of subject representation, the analyzed software does not contemplate pragmatic dimensions essential to contextual meaning, indicating a gap and an opportunity for the development of interdisciplinary approaches that integrate pragmatics, informational semiotics, and natural language processing.
Pragmatic-linguistics in natural language processing: contributions to subject representation
Keywords: Organização da informação; Tratamento temático da informação; Pragmática; Processamento da linguagem natural; Linguística - Processamento de dados; Indexação automática; Information organization; Pragmatics; Computational linguistics; Automatic indexing